Contemporary young motherhood: experiences of hostility - Fearnley, Barry (Journal of children's services, 2018)
Purpose The purpose of this paper is to illustrate the hostility many young women who are also mothers experience within their everyday lives. Design/methodology/approach The paper will draw on qualitative research, incorporating a narrative approach, to illustrate the hostility many young mothers experience on a daily basis. The research design included a focus group, semi-structure interviews and participant observations. Findings The paper reports the findings of a study that explored the experiences of young women who are also mothers. The author presents the findings that indicate that many young women, who are also young mothers, experience hostile reactions and interactions as part of their everyday lives. Research limitations/implications The small sample size means that this study cannot be generalised, but it does contribute to the growing body of qualitative evidence in relation to young mothers. Practical implications The findings suggest that there needs to be more recognition and acknowledgement of the hostility young women experience. Such hostility could have deleterious consequences on the young women, their parenting ability and also on the children. Originality/value This paper documents the experiences of young women who are also mothers and how they experience hostility as a daily occurrence. The hostility ranged from verbal to non-verbal and how they felt they were being treated, inferences about their sexuality to stereotyping.